Synthesis and crystal structure of 1-((3R,10S,13S, 17S)-3-((2-methoxyphenyl)amino)-10,13-dimethylhexadecahydro-1H-cyclopenta[α]phenanthren-17-yl)ethan-1-one, C28H41NO2 - Ye Jiang-Hai; Chen Ren-Song; Zhang Wen-Wen; He Kang; Zou Juan (Zeitschrift für Kristallographie - New Crystal Structures)
C28H41NO2, monoclinic, C2 (no. 5), a = 4.8622(5) Å, b = 6.7853(7) Å, c = 14.3349(17) Å, β = 96.556(3)°, V = 469.84(9) Å3, Z = 2, R gt(F) = 0.0482, wRref (F 2) = 0.1257, T = 284(2) K.